Growth of Government And The Politics of Fiscal Policy - Chetan Ghate; Paul J. Zak (Claremont McKenna College, Department of Economics, 2000)
U.S. government expenditures increased rapidly during the post-war period, then slowed in the 1980s and began falling in 1992. To examine the dynamics of the growth and subsequent reduction in government spending, we present a dynamic general equilibrium model in which politicians choose government spending to maximize support by their constituents. The model predicts that government expenditures will initially mimic Wagner's law - the tendency for government spending to increase with GDP - but eventually diverge from output due to the growth of the welfare state. After government expenditures become large, we identify an endogenous threshold on the economy's growth path where it is optimal for politicians to shrink the welfare sate, cut taxes, and stimulate output growth. We show that the policies chosen by politicians are Pareto suboptimal and cause endogenous cycles in output. Such cycles are of several types, and we characterize when the equilibrium growth path will result in a reduction in the size of the welfare state, as well as when the welfare state cycles between small and large.
Keywords: P16; E62; O40; 330; government expenditures; growth; Wagner's Law; endogenous cycles